The video-rate imaging of sub-10 nm plasmonic nanoparticles in a cellular medium free of background scattering. Issue 8 (18th January 2021) - Gao, He; Wu, Pei; Song, Pei; Kang, Bin; Xu, Jing-Juan; Chen, Hong-Yuan
Abstract : An absorption modulated scattering microscopy technique that allows for the imaging of sub-10 nm gold nanoparticles within a cellular scattering medium is presented. Abstract : Plasmonic nanoparticles ( e.g., gold, silver) have attracted much attention for biological sensing and imaging as promising nanoprobes. Practical biomedical applications demand small gold nanoparticles (Au NPs) with a comparable size to quantum dots and fluorescent proteins. Very small nanoparticles with a size below the Rayleigh limit (usually <30–40 nm) are hard to see by light scattering using a dark-field microscope, especially within a cellular medium. A photothermal microscope is able to detect very small nanoparticles, down to a few nanometers, but the imaging speed is usually too slow (minutes to hours) to image living cell processes. Here an absorption modulated scattering microscopy (AMSM) method is presented, which allows for the imaging of sub-10 nm Au NPs within a cellular medium. The unique physical mechanism of AMSM offers the remarkable ability to remove the light scattering background of the cellular component. In addition to having a sensitivity comparable to that of photothermal microscopy, AMSM has a much higher imaging speed, close to the video rate (20 fps), which allows for the dynamic tracking of small nanoparticles in living cells. This AMSM method might be a valuable tool for living cell imaging, using sub-10 nm Au NPs as biological probes, and thereby unlocking many new applications, such as single molecule labeling and the dynamic tracking of molecular interactions.